2018
DOI: 10.2147/copd.s176173
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference on the knowledge, attitude, and practice of COPD diagnosis and treatment: a national, multicenter, cross-sectional survey in China

Abstract: PurposeTo investigate the gender difference in knowledge, attitude, and practice of COPD diagnosis and treatment in China.Patients and methodsA nationwide, multicenter, cross-sectional questionnaire study was carried out to investigate patients’ understanding and experience of COPD between September 2007 and December 2008.ResultsTwo thousand and seventy-two patients were recruited from eleven centers. The final effective questionnaires were those of 1,698 cases, of which 32% were female. Women were younger, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
(38 reference statements)
4
18
0
Order By: Relevance
“…Women instead, despite better knowledge of diseases, reported lower satisfaction with social support and lower quality of life. [37][38][39][40] Confirming that, our study has shown that some factors traditionally associated with higher or lower adherence to therapy have a different impact in the two sexes.…”
Section: J O U R N a L P R E -P R O O F 43 Sex-specific Differencessupporting
confidence: 83%
“…Women instead, despite better knowledge of diseases, reported lower satisfaction with social support and lower quality of life. [37][38][39][40] Confirming that, our study has shown that some factors traditionally associated with higher or lower adherence to therapy have a different impact in the two sexes.…”
Section: J O U R N a L P R E -P R O O F 43 Sex-specific Differencessupporting
confidence: 83%
“…11,14 This was not the case for the PFT results in our study population, in which males had worse FEV 1 and FEV 1 /FVC values than females, a finding consistent with nationwide multicenter studies from Spain and China. 14,15 The discordance between symptom and exacerbation rate on one hand, and the PFT results on the other, may be due to a higher rate of asthma-COPD overlap in females, as observed in this and other studies. 28,29 Several population-based studies have reported steeper annual FEV 1 declines in men than in women.…”
Section: Discussionsupporting
confidence: 60%
“…[11][12][13] However, despite having better lung function, female COPD patients suffer from a larger number of symptoms and more frequent exacerbations. 3,14,15 These features may be related to the socioeconomic status of each study population and thus its specific risk factors. Korea has rapidly changed from a developing to a developed country, so it may have unique features not only in terms of COPD but also its occurrence in males vs females.…”
Section: Introductionmentioning
confidence: 99%
“…Female patients develop COPD at earlier ages with lower tobacco consumption in comparison to males [4], and their quality of life is more impaired [25]. Females have an increased susceptibility to COPD due to sex-related biological factors [26] and may have different responses to medical treatment, follow-ups, smoking cessation interventions and pulmonary rehabilitation programmes [27][28][29][30][31][32]. Women with COPD exacerbations are younger, smoke more actively and have less comorbidity [33].…”
Section: Discussionmentioning
confidence: 99%